University proceedings. Volga region. Social sciences - E.S. Plakhova (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. To date, the annual report is a working tool of all Russian ombuds-men. Similarly, for the Commissioner for the Protection of the Rights of Entrepreneurs un-der the President of the Russian Federation (hereinafter referred to as the Commissioner), the annual report plays an important role in summarizing the work, identifying the prob-lems of the business community, as well as ways to solve them. The purpose of the work is a comprehensive analysis of the report of the business Ombudsman, an in-depth study of the successes and problems of regional business, theoretical and practical problems of the institute as a whole. Materials and methods. It is worth defining the concept of “reportˮ, which will be used in the article later. The report is a text and (or) graphic material on the results of the Commissioner's activities, containing an assessment of the conditions for conducting business in the Russian Federation, as well as proposals to improve the legal status of business entities in the part related to the competence of the Commissioner. It re-flects general provisions, systemic problems that have been identified or solved for several years, as well as the main provisions of the reports of regional ombudsmen. The article pre-sents key successes and achievements, as well as problems of regional business on the ex-ample of the Penza region, Samara region, Orenburg region and Nizhny Novgorod region, and also briefly touches on the republican regions, including the Republic of Dagestan. Conclusions. The author combines the positions of various legal scholars, including those studying the institutes of the Commissioner for Human Rights and the Rights of the Child. Draws conclusions about the impact of the institute on the development of legislation on entrepreneurial activity.